Análise da eficiência técnica da estratégia competitiva de uma clínica de medicina do trabalho no Estado do Ceará - Moreira, Samuel Thadeu Góes (2014)
Health is an important factor for the development and well-being of a society. During the building of a model of optimal health, we must invest heavily in measures aimed at the practice of preventive medicine. Occupational Medicine is one of the sectors of Preventive Medicine has shown that most growth, with the advent of more stringent labor laws that appreciate the health and safety of workers. With this growth, the competitiveness of the private institutions of Safety and Occupational Medicine market began to demand more control and efficiency within the Health Economic Industrial Complex formed in Brazil. It becomes necessary to study strategies to improve the functioning of these institutions. The model of Competitive Strategy of the american economist Michael Porter became popular, since its inception in 1970, among those strategies that contribute to the prominent of the enterprises in a competitive market. In order to study the technical efficiency of Competitive Strategy applied in an enterprise of Occupational Medicine, in Fortaleza - Ce, from the evolution of its revenues in the years 2010-2013, this Case Study is maked.